Children’s participation in judicial procedure to prevail family justice - Ahmad A.; Awal N.A.M.; Samuri M.A.A.; Rajuddin A.S.; Yaakob A.; Zakaria M.Z. (American Scientific Publishers, 2024)
Indexed by SCOPUS